A Test of Positive Feedback Trading among Foreign Portfolio Investors in Nigeria - Abdulkadir, Rihanat Idowu (Gadjah Mada International Journal of Business, 2023)
It has been established in the literature that the trading behavior of international investors may increase market vulnerability, especially for emerging markets. Consequently, this study examines whether positive feedback trading exists in the Nigerian stock market. Both descriptive and inferential analyses are carried out on monthly data covering the period 2013 to 2020. Specifically, the ARDL bounds testing approach is employed. Findings indicate that positive feedback trading exists in the market, as stock returns have positive and significant influence on foreign portfolio inflows. The results further show that this trading pattern becomes more prominent with rising economic growth. The findings again reveal that the exchange rate and the interest rate explain the foreign portfolio inflows in the Nigerian market. The study’s outcomes lend support for the pull theory in explaining the foreign portfolio inflow. However, no evidence is found in support of the push theory, as an explanation for the foreign portfolio inflow as the “OPEC basket crude oil price” is insignificant. It is thereby recommended that regulators should adopt measures that will help foreign investors to be better informed about the Nigerian market, in order to reduce their positive feedback trading behavior. Moreso, there is a need for the government to put in place policies targeted toward enhancing the growth of the stock market and the economy. In this way, the negative impact of such trading behavior will be minimal, as short-term trading by foreign investors will be reduced and the foreign portfolio inflows will be sustainable.